What Motivates Indonesian Students to Become COVID-19 Volunteers? A Pandemic Study - M. Nurdin Zuhdi; Fitria Siswi Utami; Iwan Setiawan (Journal of Health Sciences and Medical Development, 2023)
Becoming a volunteer is one of the efforts to encourage people directly help in humanitarian programs. Universitas Aisyiyah (UNISA) Yogyakarta has sent hundreds student volunteers from various study program during COVID-19 pandemic in 2021-2022. Concerning the risk as volunteer, it is worthy to appreciate their motivation to engage the program. This study determine the motivation become COVID-19 volunteer among UNISA Yogyakarta students. A descriptive study design with 53 respondents was conducted to answer the objective. This study showed that students were in adequate motivation become COVID-19 volunteers. They perceive that become volunteer is a real action of caring with others. They do not need take long time to make a decision become a volunteer. Future research exploring the management of volunteer is needed.